rHuEPO Hyporesponsiveness and Related High Dosages Are Associated with Hyperviscosity in Maintenance Hemodialysis Patients - Mehtap Erkmen Uyar; Selami Kocak Toprak; Hatice Saglam; Emre Tutal; Meltem Bay; Osman Ilhan; Zeynep Bal; Siren Sezer (The Scientific World Journal)
Objective. Increased viscosity may increase the risk of thrombosis or thromboembolic events. Recombinant human erythropoietin (rHuEPO) is the key stone treatment in anemic ESRD patients with the thrombotic limiting side effect. We evaluated the influence of clinical and laboratory findings on plasma viscosity in MHD patients in the present study. Method. After applying exclusion criteria 84 eligible MHD patients were included (30 female, age: years). Results. Patients with high viscosity had longer MHD history, calcium × phosphorus product, and higher rHuEPO requirement (356.4 versus 204.2 U/kg/week, : 0.006). rHuEPO hyporesponsiveness was also more common in hyperviscosity group. According to HD duration, no rHuEPO group had the longest and the low rHuEPO dosage group had the shortest duration. Despite similar Hb levels, 68% of patients in high rHuEPO dosage group; and 38.7% of patients in low rHuEPO dosage group had higher plasma viscosity (: 0.001). Patients with hyperviscosity had higher rHuEPO/Hb levels (: 0.021). Binary logistic regression analyses revealed that rHuEPO hyporesponsiveness was the major determinant of hyperviscosity. Conclusion. We suggest that the hyperviscous state of the hemodialysis patients may arise from the inflammatory situation of long term HD, the calcium-phosphorus mineral abnormalities, rHuEPO hyporesponsiveness, and related high dosage requirements.